Book Reviews - Collis, Leo and Daseler, Graham and Lake, Carolyn and Owen, Jez and Dator, Robert Kenneth and Kabanova, Daria and Kramer, Gary M. and Larke-Walsh, Dr George and O’Brien, Adam (Film International, 2012)
Tashlinesque: The Hollywood Comedies of Frank Tashlin, Ethan de Seife, (2012) Middletown, CT: Wesleyan University Press, 251pp., ISBN: 9780819572400 (hbk), $35, ISBN: 9700819572437 (e-book), $16.99John Huston: Courage and Art, Jeffrey Meyers, (2011) New York: Crown Archetype, 475 pp., ISBN: 9780307590671 (hbk), $30‘Halsted Plays Himself, William E. Jones, (2011) Los Angeles, CA: Semiotext(e)/Native Agents Series, 200pp., ISBN: 9781584351078 (pbk), $24.95Cinema & Colour: The Saturated Image, Paul Coates, (2010) London: Palgrave Macmillan (on behalf of British Film Institute), 184pp., ISBN: 9781844573141 (pbk), £16.99Taking Place: Location and the Moving Image, John David Rhodes and Elena Gorfinkel (eds), (2011) Minneapolis: University of Minnesota Press, 392pp., ISBN: 9780816665174 (pbk), $27.50Directory of World Cinema: Spain, Lorenzo J. Torres Hortelano (ed.), (2011) Bristol: Intellect, 287pp., ISBN: 9781841504636 (pbk), $25.00Shadows of Progress: Documentary Film in Post-War Britain, Patrick Russell and James Piers Taylor (eds), (2010) London: Palgrave MacMillan on behalf of the BFI, 429pp., ISBN: 9781844573219 (pbk), £20.99, ISBN: 9781844573226 (hbk), £62.50Hollywood Cinema and the Real Los Angeles, Mark Shiel, (2012) London: Reaktion Books, 336pp., ISBN: 9781861899026 (hbk), £25.00
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9maW50LjEwLjQtNS4xMjhfNA